Interactive PowerPoint Multimedia Based on ISpring Suite to Improve Social Studies Learning Outcomes for VI Grade Elementary Schools - Yulia Astuti Dewi, Ni Luh Putu; Desak Putu Parmiti; I Gusti Ayu Tri Agustiana (International Journal of Elementary Education, 2024)
The lack of learning media has an impact on low student social studies learning outcomes. This study aims to analyze the effectiveness of interactive PowerPoint multimedia based on iSpring Suite on learning outcomes in the subject of social studies with ASEAN material for grade VI in elementary schools. The subjects in this study consisted of 3 lecturers as material experts, 3 lecturers as media experts, 3 lecturers as learning design experts, 3 teachers as expert practitioners, 3 grade VI students in individual trials, and 9 grade VI students in small group trials. This study uses the ADDIE development model. The data collection method used in this study is the questionnaire and test method. The results of the study with the correlated t-test obtained a t count of 7.25 greater than the t table value so that H0 was rejected and H1 was accepted. The N-gain score test of the pretest and posttest data obtained an N-gain score of 56.1%, which is included in the fairly effective category. So, it can be concluded that media development is very valid, practical and quite effective in being applied to the content of social studies with ASEAN material for grade VI of elementary schools in improving student’s cognitive learning outcomes.